IMPLIKASI PEMBERLAKUAN UNDANG-UNDANG NO. 9 TAHUN 2015 TENTANG PERUBAHAN KEDUA UNDANG-UNDANG NO. 23 TAHUN 2014 TENTANG PEMERINTAH DAERAH ATAS PERIZINAN PERTAMBANGAN TERHADAP LEGISLASI DI DAERAH - Nurul Laili Fadhilah (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2016)
Mines that have high economic value make various circles of society are encouraged to explore and exploit the natural resources that contains the value of the mine, including in the government both central and local governments at the provincial, regency / municipality assumed to get the local revenue of funding sources of mining in the area. Post implementation of Law No. 9 Year 2015 on the second amendment of Law No. 23 Year 2014 on Regional Government where it is implicated in the change of authority in the regions in terms of mining licensing authority in the area. Where the regime of local government legislation old one is still under the authority of the district / city, but after the enactment of new local government authority for granting mining licenses are no longer under the authority of district / city yet become the authority of the provincial government. The above conditions provide regulatory impact in the region to immediately follow up the enforcement of laws that the new government as a new regulation DOI: http://dx.doi.org/10.17977/um019v1i22016p091